Improving the green public procurement performance of Chinese local governments: From the perspective of officials' knowledge. Issue 3 (June 2019) - Liu, Junqi; Shi, Benshan; Xue, Jinjie; Wang, Qi
Abstract: Green public procurement (GPP) is one of the crucial environmental policy tools for sustainability. Although GPP has been implemented in many developing countries, its performance is in urgent need of improvement. This study focuses on the perspective of procurement officials' knowledge and develops a new conceptual model with direct and moderating effects to explore factors that may affect Chinese procurement officials' GPP performance. Using data collected from 139 Chinese local government officials and employing hierarchical regression analysis, this study finds that procurement officials' awareness of GPP implementation policies exerts a positive, direct impact on their GPP performance. Procurement officials' receiving GPP training and working in local governments included in a mature China national sustainable community (CNSC) program can positively moderate the relationships between their awareness of GPP implementation policies and GPP performance. However, awareness of GPP-related regulations does not have the same effect. Meanwhile, even the mature CNSC program cannot exert a positive, direct impact on GPP performance. This study deepens the research on influence factors of GPP performance, the policy implications can be useful for policymakers in China and other developing countries. Highlights: We develop a conceptual model for factors affecting GPP performance. The perspective of this study is officials' knowledge. The awareness of GPP policies exerts positively direct impact on GPP performance. GPP training and CNSC program both have moderation effect. CNSC program fails to exert direct impact on GPP performance.